Selling the Korean War propaganda, politics, and public opinion in the United States 1950-1953 - Casey, Steven (Oxford University Press, 2008)
How presidents spark and sustain support for wars remains an enduring and significant problem. Korea was the first limited war the U.S. experienced in the contemporary period, and in 'Selling the Korean War', Steven Casey explores how Presidents Truman and Eisenhower tried to sell it to the American public.